Synergistic Activity of Vancomycin and Gentamicin Against Staphylococcus aureus Biofilms on Polyurethane Surface - Nicolas Henrique Borges; Paula Hansen Suss; Gabriel Burato Ortis; Leticia Ramos Dantas; Felipe Francisco Tuon (Microorganisms)
Staphylococcus aureus are frequently associated with biofilm formation on intravascular devices. Biofilms limit antimicrobial penetration and promote phenotypic resistance, challenging conventional treatment strategies. Vancomycin (VAN) and gentamicin (GEN) have been used clinically, but their combined antibiofilm activity remains underexplored. This study evaluates the efficacy of VAN and GEN, alone and in combination, against biofilms formed by methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) on polyurethane. MICs were determined for VAN and GEN. Biofilm biomass and metabolic activity were quantified using crystal violet and MTT assays, respectively. Biofilm viability was assessed through fluorescence microscopy and a modified Calgary Biofilm Device. A continuous-flow peristaltic model was developed to test treatment under simulated catheter conditions. While monotherapy with VAN or GEN had modest effects, their combination significantly reduced biomass and metabolic activity. VAN 20 mg/L + GEN 8 mg/L and VAN 40 mg/L + GEN 8 mg/L achieved over 70% reduction in MRSA biofilm viability and complete eradication in MBEC assays. Dynamic model assays confirmed biofilm reduction with combination therapy. The combination of VAN/GEN exhibits synergistic antibiofilm activity against S. aureus, particularly MRSA. These findings support its potential application in catheter salvage strategies, including antibiotic lock therapy.